Community participation in quality assessment for green open spaces in Malaysia - Abdul Malek, Nurhayati; Mariapan, Manohar; Ab Rahman, Nik Ismail Azlan (Elsevier, 2015)

(untitled)
This study validates the use pattern scales for green open spaces in Malaysia. The measures on use pattern were developed using three use pattern scales, which are activities, passive activity and active activity. Samples of 414 daily park users were analyzed using Confirmatory Factor Analysis (CFA) to validate the instrument. Results showed good-fit indices on each construct confirming the theory behind each and every item used in the study. Despite several reductions on the items, the CFA on use pattern yield good internal consistencies making it suitable for its use in the research design focusing in measuring the use pattern from the community participation aspect of neighbourhood green.